Self-Assessment dalam Kegiatan Diskusi Problem-Based Learning Fakultas Kedokteran: Kajian Naratif - Rose Feri; Marcellus Simadibrata; Anwar Jusuf (Jurnal Pendidikan Kedokteran Indonesia, 2015)
Background: Student peformance assessment during problem-based learning (PBL) discussion is still debatable. One of the assessments that applies adult learning principle is self-assessment  (SA). In fact, many medical schools prefer to use tutor assessment than SA because it is considered less accurate. Many studies have reported that the accuracy of SA is poor because of their own lack of knowledge and SA skills.  This literature review aims to explore deeper in SA and its basic principles in designing SA instrument for PBL discussion in medical school.